Species Diversity of Dickeya and Pectobacterium Causing Potato Blackleg Disease in Pakistan - Sarfraz, Sohaib (Plant disease, 2020)
Potato blackleg is caused by a diverse species of pectinolytic bacteria. In Pakistan, approximately 90% of the pathogens involved belong to Pectobacterium atrosepticum. Survey (2014 to 2017), sampling, and isolation from different potato growing areas of Punjab, Pakistan depicted an overall disease incidence of approximately 15%. Thirty-six pectinolytic strains confirmed through biochemical and pathogenicity testing were characterized via gapA gene to identify them at the species level. To further validate the identification, one strain from each species SS26 (P. atrosepticum), SS28 (Pectobacterium polaris), SS70 (Dickeya dianthicola), SS90 (Pectobacterium parmentieri), SS95 (Pectobacterium punjabense), and SS96 (Pectobacterium versatile) were selected for draft genome sequencing and multilocus sequence analysis of 13 housekeeping genes (fusA, rpoD, acnA, purA, gyrB, recA, mdh, mtlD, groEL, secY, glyA, gapA, and rplB). Phylogenetic analysis revealed considerable genetic diversity in the genus Pectobacterium. In silico DNA-DNA hybridization and average nucleotide identity values of the strains selected for genome sequencing were determined with other reference Pectobacterium and Dickeya strains. Moreover, all six representative strains were also phenotypically characterized on the basis of metabolism of different carbon sources. Overall, on the basis of genotypic and phenotypic characteristics, these 36 isolates were grouped into six species: P. atrosepticum, P. versatile, P. parmentieri, P. polaris, P. punjabense, and D. dianthicola